2021
DOI: 10.1136/bmjopen-2021-052728
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: the Acquired Brain Injury Community REhabilitation and Support Services OuTcomes CohoRT (ABI-RESTaRT), Western Australia, 1991–2020

Abstract: Purpose Transition back into the community following acute management of acquired brain injury (ABI) is a critical part of recovery. Post-acute rehabilitation and transitional care can significantly improve outcomes. The Acquired Brain Injury Community REhabilitation and Support Services OuTcomes CohoRT (ABI-RESTaRT) is a novel whole-population cohort formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…ABI-RESTaRT is a retrospective whole-population cohort study of all individuals aged 18–65 years who received post-acute care through Brightwater Care Group from inception in 1991 to 31 December 2020 ( n = 1,011) ( 18 ). Inclusion criteria were English speaking and a primary diagnosis of TBI, NTBI, or eligible neurologic condition, defined by Australian Rehabilitation Outcomes Center impairment codes ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ABI-RESTaRT is a retrospective whole-population cohort study of all individuals aged 18–65 years who received post-acute care through Brightwater Care Group from inception in 1991 to 31 December 2020 ( n = 1,011) ( 18 ). Inclusion criteria were English speaking and a primary diagnosis of TBI, NTBI, or eligible neurologic condition, defined by Australian Rehabilitation Outcomes Center impairment codes ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Demographic and clinical variables were extracted from EMRs and linked Hospital Morbidity Data Collection (HMDC) and Emergency Department Data Collection (EDDC) records from the WA Data Linkage System ( 20 ). Full details are presented elsewhere ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, an episode of CNS infection can lead to an ABI, wherein neuroglial cell damage occurs due to a combination of infection directly and the associated immune response 8 . ABI can lead to functional disability in survivors, and globally millions suffer from long‐term physical, cognitive and psychosocial sequelae secondary to neurological infection 9 .…”
Section: Figurementioning
confidence: 99%
“…[5][6][7] Specifically, an episode of CNS infection can lead to an ABI, wherein neuroglial cell damage occurs due to a combination of infection directly and the associated immune response. 8 ABI can lead to functional disability in survivors, and globally millions suffer from long-term physical, cognitive and psychosocial sequelae secondary to neurological infection. 9 In the UK, multicentre studies have shown reduced quality of life following episodes of meningitis and encephalitis, with long-term mental health issues and neurocognitive dysfunction being common.…”
mentioning
confidence: 99%